المجاورون الجزائريون بالحرمين الشريفين في القرنين في القرنين 8و9هـ/14و15م - سليماني عبد القادر (University Of Eloued جامعة الوادي, 2023)
الملخص : يتناول هذا المقال موضوع المجاورة في الحرمين الشريفين ، بما تحمله من أبعاد دينية و تاريخية و جغرافية ، وبما تمثله من تمظهر حضاري مهم في التواصل بين مختلف أرجاء العالم الإسلامي ، وقد كان التركيز هنا على مجاوري المغرب الأوسط (الجزائر)، في القرنين 8و9هـ/14و15م ، و الأدوار التي اضطلعوا بها في بلاد الحرمين في المجالات العلمية و الاجتماعية على وجه الخصوص، و قد كشفت الدراسة عن جملة من النتائج المتنوعة التي تمحورت بين تبيين حجم ظاهرة المجاورة ، و الكشف عن الأدوار المهمة التي لعبها المجاورون في المجتمعين المكي و المدني ، في الحياة الاجتماعية و العلمية ، فضلا عن فكرة التواصل و التبادل الحضاري بين جناحي العالم الإسلامي آنذاك. This article deals with the issue of neighborhood in the Two Holy Mosques, with its religious, historical and geographical dimensions, and whith it's representation of an important cultural phenomenon in communication between different parts of the Islamic world. The focus here was on the neighbors of the Middle Maghreb (Algeria), in the 8th and 9th centuries AH / 14th and 15th centuries BC And the roles they played in the land of the Two Holy Mosques in the scientific and social fields in particular. The study revealed a number of diverse results that centered between showing the size of the phenomenon of neighborhood, and revealing the important roles played by neighbors in the Meccan and medinian societies, in social and scientific life, as well as the idea of communication and cultural exchange between the two wings of the Islamic world at the time. .
الأدوار الإجتماعية و العلمية
Keywords: المجاورون; الأوقاف; الجزائر; الحياة العلمية; الحرمان الشريفان; Neighbors; Middle Maghreb; Endowment; Scientific life; Society